Estruturação do observatório brasileiro vitivinícola - Poletto, Graziela (My University, 2019)
The ability to face changes by developing competencies to adapt has been presented as one of the greatest challenges for organizations. Market internationalization and rapid technological progress lead organizations to the imperative of anticipation rather than adaptation. In this sense, the use of information in order to foresee trends arises categorically so that organizations can be prepared and be able to develop appropriate strategies. This movement has resulted in the creation of observatories, which are systems organized to follow the evolution of a phenomenon. It is not different in the wine sector and the responsibility to meet this demand relies on Ibravin (Brazilian Wine Institute), a representative institution that connects the links of the production chain including winegrowers, winemakers and entities. The objective of this work is to provide the wine sector with a platform that supports its development through the observatory structuration. The Brazilian Wine Observatory (OBVV) emerges as a solution to provide the sector with reliable and current information, both retrospective and prospective, which also closes a theoretical gap in the lack of studies on the structuring of observatories. It centralizes and provides information with systematized search and easy access to users. In addition, it is possible to share information obtained in events that raise risky situations to wine sector. This dissertation presents the mapping of the existing observatories, the definition of the ideal model for Ibravin, with its foci and sources and concludes with the construction of the platform. The consolidation of the OBVV is expected to promote the strengthening of governance and the continuity of a self-sustainable wine management, to value the services provided by Ibravin to part of a chain and to leverage the insertion of Brazilian products movement in the international market.
A capacidade de enfrentar mudanças, desenvolvendo competências para se adaptar, tem sido apresentada como um dos maiores desafios para as organizações. A internacionalização dos mercados e a aceleração do progresso tecnológico conduz as organizações ao imperativo da antecipação e não mais da adaptação. Neste sentido, a utilização da informação para antecipar tendências surge categoricamente para que as organizações estejam preparadas e saibam desenvolver estratégias adequadas. Este movimento tem gerado a criação dos observatórios, que são sistemas organizados para acompanhar a evolução de um fenômeno. No setor vitivinícola não é diferente e a responsabilidade por atender a esta demanda recai sobre o Instituto Brasileiro do Vinho (Ibravin), entidade representativa que reúne os elos da cadeia, sendo viticultores, vinicultores e entidades. Assim, o objetivo deste trabalho é subsidiar o setor vitivinícola com uma plataforma que sustente seu desenvolvimento através da estruturação de um observatório. O Observatório Brasileiro Vitivinícola (OBVV) surge como uma solução que alimenta o setor com informações confiáveis e atuais, tanto retrospectivas quanto prospectivas e que supre uma lacuna teórica de falta de estudos sobre estruturação dos observatórios. Ele centraliza e disponibiliza informações com busca sistematizada e de fácil acesso aos seus usuários. Além disso, é possível compartilhar informações obtidas em eventos que levantem situações que possam demonstrar riscos ao setor vitivinícola. Esta dissertação apresenta o mapeamento dos observatórios existentes, a definição do modelo ideal para o Ibravin, com seus focos e fontes e finaliza com a construção da plataforma. Almeja-se que a consolidação do OBVV promova o fortalecimento da governança e a continuidade da gestão vitivinícola de forma autossustentável, ou seja, que valorize os serviços prestados pelo Ibravin a todos os atores da cadeia vitivinícola e alavanque o movimento de inserção dos produtos brasileiros no mercado internacional.
Keywords: Inteligência competitiva (Administração); Indústria vinícola; Business intelligence; Wine industry